A deeper dive into the blue economy: the role of the diving sector in conservation and sustainable development goals - Forrest, Matthew J.; Favoretto, Fabio; Nisa, Zahidah A.; Aburto-Oropeza, Octavio (Frontiers in Marine Science, 2023)
Attaining an equitable Blue Economy requires reconsidering historical extractive usages of natural ocean capital in favor of more sustainable activities. Scuba diving is an expanding industry, and several examples illustrate how the diving sector has assisted with transitions to sustainable economic activities. In certain countries diving tourism generates revenues comparable with fishing industries, yet the sector remains underrepresented within marine conservation efforts. Therefore, we present five actions tailored to enhance the diving sector’s participation in the Blue Economy: i) Organize the fragmented sector via international associations and federations; ii) Recognize usage rights for natural capital equal to extractive activities; iii) Modernize the sector using technology to improve connectivity and data sharing; iv) Invest in the sector by engaging private and public funding and subsidizing critical infrastructure to enable equitable access; v) Foster a sense of community by training and supporting local leaders, thereby ensuring more equitable participation by including women, indigenous people, and the youth. Diving represents one of the only endeavors that enables citizens to actively support the Blue Economy and help to achieve the United Nations Sustainable Development Goal 14, “Life Below Water”; therefore, the diving sector is uniquely poised to help address conservation goals and sustainable development.